The implementation of stabilization policy - Olivier Loisel (Theoretical Economics, 2021)
In locally linearized dynamic stochastic rational-expectations models, I introduce the concepts of feasible paths (paths on which the policy instrument can be expressed as a function of the policymaker's observation set) and implementable paths (paths that can be obtained, in a minimally robust way, as the unique local equilibrium under a policy-instrument rule consistent with the policymaker's observation set). I show that, for relevant observation sets, the optimal feasible path under monetary policy can be non-implementable in the New Keynesian model, while constant-debt feasible paths under tax policy are always implementable in the Real Business Cycle model. The first result sounds a note of caution about one of the main lessons of the New Keynesian literature, namely the importance for central banks to track some key unobserved exogenous rates of interest, while the second one restores to some extent the role of income or labor-income taxes in safely stabilizing public debt. For any given implementable path, I show how to design arithmetically a policy-instrument rule consistent with the policymaker's observation set and implementing this path as the robustly unique local equilibrium.
Keywords: E32; E52; 330; Stabilization policy; local-equilibrium determinacy; observation set; feasible path; implementable path; optimal monetary policy; debt-stabilizing tax policy